Multidimensional scaling analysis identifies pathological and prognostically relevant profiles of circulating T‐cells in chronic lymphocytic leukemia. Issue 10 (18th April 2014) - Rissiek, Anne; Schulze, Christian; Bacher, Ulrike; Schieferdecker, Aneta; Thiele, Benjamin; Jacholkowski, Anita; Flammiger, Anna; Horn, Christiane; Haag, Friedrich; Tiegs, Gisa; Zirlik, Katja; Trepel, Martin; et al.
<x xml:space="preserve">Abstract</x> Antitumor immunity in chronic lymphocytic leukemia (CLL) is hampered by highly dysfunctional T‐cells. Although certain T‐cell subsets have been reported to be of prognostic significance in this disease, their interplay is complex and it remains incompletely understood which of these subsets significantly drive CLL progression. Here, we determined immunological profiles of 24 circulating T‐cell subsets from 79 untreated individuals by multiparametric flow cytometry. This screening cohort included healthy donors, patients with monoclonal B‐cell lymphocytosis (MBL), Rai 0 CLL and advanced CLL. We applied multidimensional scaling analysis as rigorous and unbiased statistical tool to globally assess the composition of the circulating T‐cell environment and to generate T‐cell scores reflecting its integrity. These scores allowed clear distinction between advanced CLL and healthy controls, whereas both MBL and Rai 0 CLL showed intermediate scores mirroring the biological continuum of CLL and its precursor stages. T‐cell stimulation and suppression assays as well as longitudinal T‐cell profiling showed an increasingly suppressive regulatory function initiating at the MBL stage. Effector function was impaired only after transition to CLL and partially recovered after chemoimmunotherapy. In an independent validation cohort of 52 untreated CLL cases, aberrant T‐cell profiles were significantly associated with shorter time to treatment independently of other prognostic parameters. Random forest modeling predicted regulatory T‐cell, gamma/delta and NKT‐cells, as well as exhaustion of the CD8+ subset as potential drivers of progression. Our data illustrate a pathological T‐cell environment in MBL that evolves toward a more and more suppressive and prognostically relevant profile across the disease stages.